Dissemination and phenotypic characterization of ESBL-producing Escherichia coli in Indonesia - Tati Ariyanti; Suhaemi Suhaemi; Sri Mulyati; Sukatma Sukatma; Sumirah Sumirah; Susan Maphilindawati Noor; Faidah Rachmawati; Prima Mei Widiyanti; Eddy Sukmawinata; Andriani Andriani; Eni Kusumaningtyas; Aswin Rafif Khairullah (Open Veterinary Journal)
Background: The alarming rise in infections caused by extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli in animals and humans poses a serious threat due to its escalating antibiotic resistance. Unveiling this problematic bacteria's prevalence and resistance patterns in animals is crucial for formulating effective control strategies and safeguarding public health.